Bilayer interface engineering through 2D/3D perovskite and surface dipole for inverted perovskite solar modules - Jiarong Wang; Leyu Bi; Xiaofeng Huang; Qifan Feng; Ming Liu; Mingqian Chen; Yidan An; Wenlin Jiang; Francis R. Lin; Qiang Fu; Alex K.-Y. Jen (eScience)
The persistency of passivation and scalable uniformity are vital issues that limit the improvement of performance and stability of large-area perovskite solar modules (PSMs). Here, we design a bilayer interface engineering strategy that takes advantage of the stability and passivation ability of low-dimensional perovskite and the dipole layer. Introducing phenethylammonium iodide (PEAI) can form 2D/3D heterojunctions on the perovskite surface and effectively passivate defects of perovskite film. Interestingly, the upper piperazinium iodide (PI) layer can still form surface dipoles on the 2D/3D perovskite surface to optimize energy-level alignment. Moreover, the bilayer interface engineering enables large-area perovskite films with uniform surface morphology, lower trap-state density and stability against environmental stress factors. The final devices achieved a small-area PCE of 25.20% and a large-area (1 ​cm2) PCE of 23.96%. A perovskite mini-module (5 ​× ​5 ​cm2 with an active area of 14.28 ​cm2) could also be fabricated to achieve a PCE of 23.19%, ranking it among the highest for inverted PSMs. Additionally, the device could retain over 93% of its initial efficiency after MPP tracking at 45 ​°C for 1280 ​h. This study successfully demonstrates a bilayer interface engineering with respective functions, offering valuable insights for producing efficient and stable large-area PSCs.